Regional connectivity, differentiation and biogeography of three species of the genus Lutjanus in the western Indian Ocean - Morallana, Jonas Moqebelo (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
Snappers of the genus Lutjanus are small to large predatory fishes occurring in inshore circumtropical and subtropical waters throughout the world. These fishes support fisheries across their distribution range. Within the Western Indian Ocean (WIO), previous studies on Lutjanus kasmira revealed limited spatial genetic differentiation, whereas Lutjanus fulviflamma showed high genetic connectivity. The phylogenetic relationships among WIO snappers are unknown. Previous studies in the Indo-Pacific (IP) did not include any WIO representatives. This study examined (1) the phylogeographic patterns in Lutjanus bohar, L. fulviflamma and L. lutjanus to understand the origins and factors influencing the distribution of diversity in the region, (2) how the physical environment, biological, and ecological factors influence genetic diversity, (3) the placement of WIO snappers in context to those from the IP, as well as the placement of taxa not included previously, (4) extent of differentiation among conspecifics from the two regions, and (5) the relationship of the Caesionidae to the Lutjanidae. Samples were sourced from across the WIO and from peripheral localities, where possible. DNA sequence data were generated from two mitochondrial gene regions (cyt-b and NADH-2) and a nuclear gene region (S7 intron 1). Data were analysed under a phylogeographic framework to examine genetic structure, diversity and differentiation among identified regions for each of the three species. Other sequence data were generated from two mitochondrial gene regions (COII and 16S rDNA) to examine the phylogenetic placement of WIO snappers in context of the IP snappers and the relationship of the Caesionidae to the Lutjanidae. Lutjanus bohar and L. fulviflamma displayed high genetic diversity, but lower diversities were observed for L. lutjanus. Genetic differentiation was observed between Mozambique and Maldives in L. bohar. Lutjanus fulviflamma was differentiated in South Africa, Mozambique, Mauritius and Thailand, while differentiation was observed between Kenya and Tanzania in Lutjanus lutjanus. Overall, low genetic differentiation and high connectivity were observed for each of the three species. This differentiation may result from intrinsic features of the species and extrinsic features of the environment, whereas the connectivity is mainly influenced by the pelagic larval duration. These patterns of differentiation are in accordance with a proposed vicariant biogeographic hypothesis for the origins of regional faunas of the IP. Phylogenies were similar to those published, with additional taxa not altering the previous groupings found. Conspecifics from the two regions clustered together, with varying degrees of differentiation among the WIO and IP, depending on the species. Members of the Caesionidae were nested within Lutjanidae, suggesting that morphological characters separating the two families are taxonomically insignificant. This affirms previous notions that the Caesionidae should be a subfamily within the Lutjanidae. This is the first multi-gene study, examining differentiation in multiple species of snapper over a wide geographic area in the WIO, and the results of this study could have potential implications for fisheries management and conservation.
Keywords: Lutjanus -- Indian Ocean; Biogeography -- Indian Ocean; Phylogeography -- Indian Ocean; Lutjanus -- Geographical distribution; Lutjanus -- Variation; Mitochondrial DNA; Animal genetics; Variation (Biology)